2017
DOI: 10.1177/1054773817717861
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Nursing Case Management in the United States

Abstract: The purpose of this study is to identify issues of case management (CM) interventions in the United States in recent studies and to identify implications for future research into CM. This study was guided by the following framework for a scoping review. Multiple electronic databases were searched to identify studies published between 2007 and 2016 in the United States and related to nursing CM. Five weaknesses were identified: no clear and consistent definition of CM, lack of theoretical frameworks, lack of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…completion of postpartum glucose tolerance test for women with gestational diabetes) contrasts with case management, which seeks to connect a patient with individualized resources depending on evolving, multi-specialty needs. 16 Furthermore, while patient advocates also help to resolve discrete individual issues about health care delivery, such as medical bills or discrimination, the long-term navigation focus is to address condition-specific needs with a particular clinical outcome in mind. 7,8,17…”
Section: Development Of Patient Navigatorsmentioning
confidence: 99%
“…completion of postpartum glucose tolerance test for women with gestational diabetes) contrasts with case management, which seeks to connect a patient with individualized resources depending on evolving, multi-specialty needs. 16 Furthermore, while patient advocates also help to resolve discrete individual issues about health care delivery, such as medical bills or discrimination, the long-term navigation focus is to address condition-specific needs with a particular clinical outcome in mind. 7,8,17…”
Section: Development Of Patient Navigatorsmentioning
confidence: 99%
“…CM has been shown to be an effective and efficient care strategy in the management of chronic illnesses for over a decade (Joo & Huber, 2018). Several systematic reviews have identified CM intervention to be effective in improving hospital utilizations, objective clinical outcomes, and psychological outcomes for patients with chronic illnesses (Hudon et al, 2019; Joo & Huber, 2018; Joo & Liu, 2019). However, there is limited evidence of how CM interventions work and what factors of CM actually affect chronic illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Case management (CM)—a “collaborative process of assessment, planning, facilitation, care coordination, evaluation, and advocacy for options and services to meet an individual’s and family’s comprehensive health needs through communication and available resources to promote quality, cost-effective outcomes” (Case Management Society of America, 2016, p. 8)—is one of the most promising (Fero et al, 2011; Hudon et al, 2019). CM has been utilized internationally as an effective, efficient, and cost-effective care coordination in the management of chronic illnesses (Hudon., 2019; Joo, 2014; Joo & Huber, 2018). Although CM activities have been delivered by nurse case managers (NCMs) and other health care practitioners, most CM is led by nurses (Park & Huber, 2009; Tahan et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 With its intensive focus on patients with multiple chronic conditions, care management is distinct from less resource-intensive disease management programs that generally oversee larger, less complex patient populations defined by a single disease (e.g., diabetes or congestive heart failure disease management programs). [10][11][12] Complex patient care management teams are typically led by a nurse and/or a licensed clinical social worker and include a comprehensive initial patient assessment to create a care plan, frequent monitoring of the patient's condition, support for transitions between care settings (e.g., hospital to home), coordination between different care providers, and education and support for patients, family members, and caregivers. 13,14 When directed towards the appropriate patients, care management is considered a powerful tool for preventing clinical deterioration and reducing future hospitalizations and costs.…”
Section: Designmentioning
confidence: 99%